MEMBANGUN MINAT BELAJAR AGAMA MASYARAKAT MELALUI PEMANFAATAN INTERNET SECARA SEHAT - Nursida, Ida (AL-IBANAH, 2021)
Among the people's habits that need to be straightened out is related to the use of the internet, that so far the use of the internet is still limited to the distribution of hobbies and fun in the form of playing online games or entertainment. Society needs to be made aware that behind this habit there are negative excesses awaiting which can damage the morality of the younger generation. The public also needs to be aware of the habits that must be built because of its positive value, namely making the internet a (religious) learning facility, namely by visiting sites that can provide enlightenment and deepening of Islamic teaching material, while maintaining a critical attitude and being careful of information sources. can not be trusted.